PERFORMANCE OF THE SECRETARIAT STAFF OF THE REGIONAL HOUSE OF REPRESENTATIVES IN YAHUKIMO REGENCY OF PAPUA PROVINCE - MATUAN, HARUN; TULUSAN, FEMMY; TAMPI, GUSTAF BUDI (Sam Ratulangi University, 2018)
The Secretariat of the Regional People's Legislative Assembly has a role in organizing secretarialadministration, administering financial administration, supporting the implementation of duties and functionsof the Regional People's Legislative Assembly, and providing and coordinating the necessary expertise of theRegional House of Representative in carrying out its functions as required. The success that is realized fromthe performance of the Secretariat of the Regional People's Legislative Assembly as a public organization willbe highly dependent on the existing staff within the organization. In reality the performance of employees willbe closely related to various things both originated from within the employee and who came from the internalorganization and environment where the organization is located. The purpose of this study to find out how theperformance of staff Secretariat of the Regional House of Representatives In Yahukimo District of PapuaProvince. The research method used in this research is qualitative method with descriptive analysis. Informantsin the study are people who can provide information about the situation and condition of the researchbackground. The research focus is seen from the indicators according to Dessler that is the quality of work, thequantity of work, the necessary supervision, the presence and the conversation. Data collection techniques usedare interview techniques, observation techniques / direct observation of the location of study, and literaturestudy. The results of the study show that the performance of the staff of the Secretariat of the Regional Houseof Representatives in Yahukimo Regency of Papua Province shows that leadership, discipline and resourcesare factors that hinder or support the performance of the Secretariat of the Regional House of Representatives.The unfavorable work strength in the archive management and the quantity of employee work has changed dueto the change of the working agenda of members of the Regional People's Legislative Assembly.Keywords : Performance, Secretariat, Regional People's Representative Assembly (DPRD)